Pride Parades : How a Parade Changed the World - Bruce, Katherine McFarland (Book collections on Project MUSE., 2016)
On June 28, 1970, 2000 gay and lesbian activists in New York, Los Angeles, and Chicago paraded down the streets of their cities in a new kind of social protest, one marked by celebration, fun, and unashamed declaration of a stigmatised identity. 45 years later, over six million people annually participate in 115 Pride parades across the United States. They march with church congregations and college gay-straight alliance groups, perform dance routines and marching band numbers, and gather with friends to cheer from the sidelines. Showcasing the voices of these participants, this book tells the story of Pride from its beginning in 1970 to 2010. Though often dismissed as frivolous spectacles, the author builds a convincing case for the importance of Pride parades as cultural protests at the heart of lesbian, gay, bisexual, and transgender (LGBT) community.